Social incentives in the workplace - Oriana Bandiera; Iwan Barankay; Imran Rasul (Institute for the Study of Labor (IZA), 2009)
We present evidence on social incentives in the workplace, namely on whether workers' behavior is affected by the presence of those they are socially tied to, even in settings where there are no externalities among workers due to either the production technology or the compensation scheme in place. To do so we combine data on individual worker productivity from a firm's personnel records with information on each worker's social network of friends in the firm. We find that compared to when she has no social ties with her co-workers, a given worker's productivity is significantly higher when she works alongside friends who are more able than her, and significantly lower when she works with friends who are less able than her. As workers are paid piece rates based on individual productivity, social incentives can be quantified in monetary terms and are such that (i) workers who are more able than their friends are willing to exert less effort and forgo 10% of their earnings; (ii) workers who have at least one friend who is more able than themselves are willing to increase their effort and hence productivity by 10%. The distribution of worker ability is such that the net effect of social incentives on the firm's aggregate performance is positive. The results suggest that firms can exploit social incentives as an alternative to monetary incentives to motivate workers.
urn:nbn:de:101:1-2009061546
Keywords: L2; M5; 330; Conformism; social incentives; social networks; Arbeitsproduktivität; Leistungsanreiz; Soziale Norm; Soziale Beziehungen; Soziales Netzwerk; Großbritannien